Synthesis and assessment of new cyclopenta-2,4-dienone derivatives for energy storage applications - Lim, Zheng Bang (2015)
A series of tetraphenylcyclopenta-2,4-dienones with various substituents including hydrogen, thiophene and methoxy groups were prepared to compare their suitability as materials for forming alkali metal- based (Li or Na) solvated electron solutions (SESs) for potential use as anode materials for flow Li-Air (or Na) batteries at ambient temperature condition. The materials are amorphous, not luminescent and have moderate Eg, opt in range 1.84–1.91 eV. They also possess good thermal stability (stable above 200 °C), exhibit quasi-reversible reduction and oxidation reactions. It was also found that the type of substituent can influence the ability of the cyclopentadienones to form SES with alkali metals, where the derivatives with hydrogen or methoxy units were found to form SESs with lithium, but the thienyl derivative did not. Parallel studies also indicated that our big π-systems were thermodynamically more favorably to solvate the electrons than small and simple aromatic or polar aprotic solvent molecules such as benzene, toluene, xylene, tetrahydrofuran, solvate acetone, etc.